Deciphering satellite observations of compressional ULF waveguide modes. Issue 4 (25th April 2016) - Elsden, T.; Wright, A. N.; Hartinger, M. D.
Abstract: We present an analytical method for determining incident and reflection coefficients for flank ULF compressional waveguide modes in Earth's magnetosphere. In the flank magnetosphere, compressional waves propagate azimuthally but exhibit a mixed standing/propagating nature radially. Understanding this radial dependence will yield information on the energy absorption and transport of these waves. We provide a step by step method that can be applied to observations of flank ULF waves, which separates these fluctuations into incident and reflected parts. As a means of testing, we apply the method to data from a numerical waveguide simulation, which shows the effect on the reflection coefficient when energy is absorbed at a field line resonance. Key Points: Derive a method for estimating incident and reflection coefficients for flank ULF waveguide modes Test method on simulation data which provide consistent results Method will be applied to satellite data in the future